Contemporary review of risk-stratified management in acute uncomplicated and complicated diverticulitis - Boermeester, Marja A.; Humes, David; Velmahos, George C.; Søreide, Kjetil (Springer, 2016)
BACKGROUND: Acute colonic diverticulitis is a common clinical condition. Severity of the disease is based on clinical, laboratory, and radiological investigations and dictates the need for medical or surgical intervention. Recent clinical trials have improved the understanding of the natural history of the disease resulting in new approaches to and better evidence for the management of acute diverticulitis.